Sensory organization of postural control after long term space flight - Shishkin, Nikita; Kitov, Vladimir; Sayenko, Dimitry; Tomilovskaya, Elena (Frontiers in Neural Circuits, 2023)
Background: Alterations in motor control systems is an inevitable consequence of space flights of any duration. After the flight, the crew-members have significant difficulties with maintaining upright balance and locomotion, which last several days following landing. At the same time, the specific mechanisms of these effects remain unclear. Objectives: The aim of the study was to assess effects of long-term space flight on postural control and to define the changes of sensory organization caused by microgravity. Methods: 33 cosmonauts of Russian Space Agency, the members of International Space Station (ISS) flights of duration between 166 and 196 days took part in this study. Computerized Dynamic Posturography (CDP) tests, which include assessment of visual, proprioceptive and vestibular function in postural stability, was performed twice before the flight and on the 3rd, 7th and 10th days after landing. The videoanalysis of ankle and hip joints fluctuations was performed to investigate the basis of postural changes. Results: Exposure to long-term space flight was followed by considerable changes of postural stability (-27% of Equilibrium Score value in the most complicated test, SOT5m). Changes in postural strategies to maintain balance were observed in the tests which provide the challenge for vestibular system. In particular, increased hip joint involvement (+100% in median value and +135% in 3rd quartile of hip angle fluctuation RMS in SOT5m) into postural control process was revealed. Conclusions: Decrease of postural stability after long-term space flight was associated with alterations in vestibular system and biomechanically was revealed by increased hip strategy which is less accurate, but simpler in terms of the central control.